Adaptive radiation of the European whitefish Coregonus lavaretus (L.) in the Pasvik watercourse: the genetic description of a new morph - Couton, Marjorie (Universitetet i Tromsø, 2012)
Sympatric occurring fish morphs in postglacial lakes usually exhibit differences in morphology and physiology driven by adaptations to differential trophic niches. The European whitefish (Coregonus lavaretus (L.)) is a highly variable fish species, with more than 200 intraspecific forms described in Europe. The morphs usually differ in their number of gill-rakers, therefore this trait has been traditionally used for whitefish classification. According to this taxonomy, three different morphs can be distinguished in northern Fennoscandia: the large sparsely rakered (LSR), the densely rakered (DR), and the small sparsely rakerd (SSR) morphs. They all exhibit differences in morphology, diet, habitat, and physiology. Recently, a new morph has been discovered in several lakes of the Pasvik watercourse which displays densely rakered gills and an external morphology similar to the LSR whitefish, and was called large densely rakered (LDR). In this study, genetic data from 18 microsatellites markers were used to evaluate the genetic differentiation and the possible origin of this new morph in three Finnish lakes of the Pasvik watercourse. The LDR morph in each lake was found to be genetically different from the three other morphs. Several possible origins were suggested, but the sympatric speciation from either the LSR or the DR morphs was the hypothesis that gained the most support from the results. Moreover, the three different LDR populations were found to have a common origin, suggesting that the divergence occurred only once after the last ice retreat and the same population divided into three when the different lakes were formed.